2013
DOI: 10.1111/jne.12001
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐Based Morphometric Analysis in Hypothyroidism Using Diffeomorphic Anatomic Registration via an Exponentiated Lie Algebra Algorithm Approach

Abstract: The present study aimed to investigate whether brain morphological differences exist between adult hypothyroid subjects and age-matched controls using voxel-based morphometry (VBM) with diffeomorphic anatomic registration via an exponentiated lie algebra algorithm (DARTEL) approach. High-resolution structural magnetic resonance images were taken in ten healthy controls and ten hypothyroid subjects. The analysis was conducted using statistical parametric mapping. The VBM study revealed a reduction in grey matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…The relation of such functional measurement to the morphometric changes of the cerebellum reported in the current study and by Singh et al [13] remains to be demonstrated. Also, the PET measurements were conducted in the resting state, i.e.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The relation of such functional measurement to the morphometric changes of the cerebellum reported in the current study and by Singh et al [13] remains to be demonstrated. Also, the PET measurements were conducted in the resting state, i.e.…”
Section: Discussionmentioning
confidence: 71%
“…A recent VBM study [13] revealed a reduction in GMV in the left postcentral gyrus and the cerebellum in 10 hypothyroid patients compared to 10 euthyroid control participants. With regard to white matter volume, a reduction was found in the cerebellum and a number of cortical regions comprising right inferior and middle frontal gyrus, right precentral gyrus, right inferior occipital gyrus and right temporal gyrus in the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the control group was used to create this template, given that control-created templates can provide greater detection accuracy than those that include all subjects, even when this control group is small (Shen et al 2007). GM and WM segmented images were registered and normalized to the template using diffeomorphisms (Singh et al 2012). This method improves the image registration, which results in a better localization and increased sensitivity in analysis (Li et al 2010).…”
Section: (Statistical Parametric Mapping Wellcome Department Of Cognmentioning
confidence: 99%
“…More recently, using voxel-based morphometry (VBM), Singh et al (25) reported reduced white-and gray-matter volumes in a small number of young adults with untreated hypothyroidism (mean age = 31.1 years). Gray matter decreases were found in the bilateral cerebellum and left postcentral gyrus, while white matter decreases were found in the bilateral cerebellum, the right precentral gyrus, right inferior and middle frontal gyrus, right inferior occipital gyrus, and right inferior temporal gyrus.…”
Section: Introductionmentioning
confidence: 97%